School climate and its influence on organizational citizenship behavior: a theoretical framework - Ismail, Suriani; Ismail, Ismi Arif; Omar, Zoharah; Alias, Siti Noormi; Md Rami, Ahmad Aizuddin (Human Resource Management Academic Research Society, 2021)
Organizational citizenship behavior (OCB) refers to the behavior of employees, which typically exceeds their official duties. This behavior is important because it helps to enhance employees’ performance and lead organizations to become more innovative and productive. Many studies on OCB have been conducted in organizations. However, limited literature can be found in the context of educational practices. Hence, the purpose of this conceptual paper is to explore deeper into OCB within an educational context. A comprehensive review of the literature has identified a factor that can potentially influence OCB, which is school climate. This paper concluded that school climate which consists of principal leadership, autonomy, teachers’ intimacy, school facilities and services positively influence OCB. The most significant contribution of this paper is the formulation of a theoretical framework which gives a deeper understanding on the relationship between school climate and OCB. The present paper proposed that more empirical studies on OCB in educational context need to be conducted to further illuminate the uniqueness of OCB within an education ecosystem.